Clinical Implication of Perineural and Lymphovascular Invasion in Rectal Cancer Patients Who Underwent Surgery After Preoperative Chemoradiotherapy. Issue 11 (24th November 2021) - Kim, Young Il; Kim, Chan Wook; Kim, Jong Hoon; Kim, Jihun; Ro, Jun-Soo; Lee, Jong Lyul; Yoon, Yong Sik; Park, In Ja; Lim, Seok-Byung; Yu, Chang Sik; Kim, Jin Cheon
Abstract : BACKGROUND: Lymphovascular and perineural invasion are well-known negative prognostic indicators in rectal cancer, but previous studies on their significance are not consistent. OBJECTIVE: This study assessed the prognostic value of lymphovascular and perineural invasion in rectal cancer patients who received preoperative chemoradiotherapy followed by curative resection. DESIGN: This is a retrospective analysis. SETTING: This study was performed at a tertiary cancer center. PATIENTS: Rectal cancer patients who underwent curative resection after preoperative chemoradiotherapy between January 2000 and December 2010. MAIN OUTCOME MEASURES: The primary outcomes were disease-free survival and overall survival. The survival rates were estimated using Kaplan-Meier analysis, and group comparisons were conducted using a log-rank test. RESULTS: Of the 1156 included patients, 109 (9.4%) presented with lymphovascular invasion and 137 (11.9%) presented with perineural invasion. Lymphovascular and perineural invasion were associated with T and N downstaging after preoperative chemoradiotherapy ( p < 0.001). In the ypN0 patients, the 5-year disease-free survival rates were 70.8% and 78.5% ( p = 0.150) for the lymphovascular invasion and absent groups, respectively. In the perineural invasion group, the 5-year disease-free survival rate was 59.0% compared to 80.2% in the absent group ( p = 0.001). Among the ypN+ patients, the 5-year disease-free survival rates were 36.9% and 44.4% for the lymphovascular invasion and absent groups, respectively ( p = 0.211). The perineural invasion group had a poorer 5-year disease-free survival rate compared to the absent group (29.7% vs 46.7%; p = 0.011). By multivariable analyses, perineural invasion correlated with a poor disease-free survival (HR 1.412, 95% CI 1.082–1.843; p = 0.011) and also in ypN0 subgroup analysis (HR 1.717, 95% CI 1.093-2.697; p = 0.019). LIMITATIONS: This study was a retrospective study conducted at a single center. CONCLUSIONS: Perineural invasion is a reliable independent predictor of recurrence in rectal cancer patients treated with preoperative chemoradiotherapy. Patients with perineural invasion should be considered for closer surveillance even with ypN0 status. See Video Abstract at http://links.lww.com/DCR/B833 . IMPLICACIÓN CLÍNICA DE LA INVASIÓN PERINEURAL Y LINFOVASCULAR EN PACIENTES CON CÁNCER DE RECTO SOMETIDOS A CIRUGÍA DESPUÉS DE QUIMIORRADIOTERAPIA PREOPERATORIA ANTECEDENTES: La invasión linfovascular y perineural en cancer de recto, son indicadores pronósticos negativos bien conocidos, pero estudios previos sobre su significancia, no son consistentes. OBJETIVO: El estudio evaluó el valor pronóstico de la invasión linfovascular y perineural en pacientes con cáncer de recto sometidos a quimiorradioterapia preoperatoria seguida de resección curativa. DISEÑO: Es un análisis retrospectivo. ENTORNO CLINICO: El estudio se realizó en un centro oncológico terciario. PACIENTES: Pacientes con cáncer de recto sometidos a resección curativa después de quimiorradioterapia preoperatoria entre enero de 2000 y diciembre de 2010. PRINCIPALES MEDIDAS DE VALORACION: Los resultados primarios fueron la supervivencia libre de enfermedad y la supervivencia general. Las tasas de supervivencia se estimaron mediante el análisis de Kaplan-Meier y las comparaciones de grupos se realizaron mediante una prueba de rango logarítmico. RESULTADOS: De los 1156 pacientes incluidos, 109 (9, 4%) presentaron invasión linfovascular y 137 (11, 9%) invasión perineural. La invasión linfovascular y perineural se asoció con reducción del estadio de T y N después de la quimiorradioterapia preoperatoria ( p < 0, 001). En los pacientes ypN0, las tasas de supervivencia libre de enfermedad a 5 años fueron del 70, 8% y el 78, 5% ( p = 0, 150) para los grupos con y sin invasión linfovascular, respectivamente. En el grupo de invasión perineural, la tasa de supervivencia libre de enfermedad a 5 años fue del 59, 0%, en comparación con el 80, 2% en el grupo ausente ( p = 0, 001). Entre los pacientes ypN +, las tasas de supervivencia sin enfermedad a 5 años fueron del 36, 9% y 44, 4% para los grupos con y sin invasión linfovascular, respectivamente ( p = 0, 211). El grupo de invasión perineural mostró una tasa de supervivencia libre de enfermedad a 5 años menor, en comparación con el grupo ausente (29, 7% versus 46, 7%, p = 0, 011). Mediante análisis multivariable, la invasión perineural se correlacionó con una pobre tasa de supervivencia de enfermedad (índice de riesgo 1, 412; intervalo de confianza del 95%: 1, 082–1, 843; p = 0, 011) y también en el análisis de subgrupos ypN0 (índice de riesgo 1, 717; intervalo de confianza del 95%: 1, 093–2, 697; p = 0, 019). LIMITACIONES: Estudio retrospectivo realizado en un solo centro. CONCLUSIONES: La invasión perineural es un predictor independiente y confiable de recurrencia en pacientes con cáncer de recto tratados con quimiorradioterapia preoperatoria. Los pacientes con invasión perineural deben considerarse para una vigilancia más estrecha incluso con estadio ypN0. Consulte Video Resumen en http://links.lww.com/DCR/B833 . (Traducción—Dr. Fidel Ruiz Healy )